Farmer learning exchange visit on agroecological farming practices in Xiengkhouang, Lao PDR - Inphonephong, Souphalack; Chounlamountry, T.; Xaydala, Viengxay; Douangsavanh, Somphasith (International Water Management Institute (IWMI). CGIAR Initiative on Agroecology; CGIAR Initiative on National Policies and Strategies, 2024)
The report documents a farmer learning exchange visit on agroecological farming practices in Xiengkhouang, Lao’s People Democratic Republic (Lao PDR), from 20–22 November 2024. It was organized by the International Water Management Institute (IWMI), under the CGIAR Initiative on Agroecology and the CGIAR Initiative on National Policies and Strategies. The visit was arranged in cooperation with the agroecology and safe food system transitions project’s implementing and commissioning team from the Department of Planning and Cooperation, the Department of Agricultural Land Management, the National Agriculture and Forestry Research Institute, the Provincial Agriculture and Forestry Office in Xiengkhouang, and CIRAD, the French Agricultural Research Centre for International Development.